Taxonomic and phylogenetic significance of leaf venation characteristics in Dioscorea plants - Sun, Xiao-Qin; Xue, Jia-Yu; Lei, Zhao; Zhang, Yan-Mei; Li, Mi-Mi; Zhou, Guang-Can; Hang, Yueyu (Archives of Biological Sciences, 2018)
We undertook a comparative study of the leaf venation characteristics of Dioscorea species from all seven sections distributed in China (33 species, 1 subspecies and 3 varieties). We established that leaf venation has a taxonomic significance in Dioscorea. The sections Combili, Opsophyton Lasiophyton and Shannicorea all show consistent acrodromous venation (a subtype of palmate venation), with Botryosicyos exhibiting consistent pinnate venation. However, sections Stenophora and Enantiophyllum show obvious intrasectional differences. For example, D. simulans and D. biformifolia of section Stenophora have acrodromously veined middle leaflets, whereas the side leaflets are pinnately veined; D. cirrhosa and D. cirrhosa var. cylindrica of section Enantiophyllum show dichotomous veinlets. Other species in the same section show either one-branched veinlets or multiple branched veinlets. In addition to the discrepancy in venation patterns, differences in many other important morphological characteristics and chemical components were also observed. Therefore, D. simulans and D. biformifolia can be reasonably excluded from section Stenophora, and section Illigerestrum can be rebuilt using these two species. In addition, D. cirrhosa and D. cirrhosa var. cylindrica should be removed from section Enantiophyllum and placed into another new section. D. simulans and D. biformifolia show pinnate venation, and the complexity of their leaf organization (with both simple and compound leaves) also points to variations between the pinnate and acrodromous veins in Dioscorea. The repeated presence of palmate and pinnate venation in multiple angiosperm clades also suggests that the formation and evolution of venation are likely the result of evolutionary adaptation to ecological environments. https://doi.org/10.2298/ABS170322058S Received: March 22, 2017; Revised: August 24, 2017; Accepted: August 24, 2017; Published online: December 26, 2017 How to cite this article: Sun X, Xue J, Lei Z, Li M, Zhang Y, Zhou G, Hang Y. Taxonomic and phylogenetic significance of leaf venation characteristics in Dioscorea plants. Arch Biol Sci. 2018;70(2):397-407.